(3GdMajX aj abg Cgd GdHjJs - (3EHQGgje Hf eMeO Hf SdjeGf Hf YHO GdGYdj GdHhSjs
(3ChdgG (B:s
(3GdMeO ddg GdPi fhQ HUGFQ Cgd hOg HfhQ gOGjJg , hTQage Yf EJHGY s
(3BNQgG (B:s
(3hjYgO ChdGOg ef hbJ Edi hbJ hMO GdEbGeI GdJi jcaQ HgG s
(3GdfSNI HgG MhGTs
(3Ydi UaMI GdZdGa Jedjcs
(3cJHJ GdYfGhjf HGdMeQIs
(3Ydi MhGTjgG JYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3abg GdePGgH GdCNQis